2022
DOI: 10.3917/anpsy1.221.0003
|View full text |Cite
|
Sign up to set email alerts
|

A French C-test for language assessment

Abstract: Short language proficiency tests are often needed for low-stakes assessment in education and research, particularly in second language settings. Vocabulary tests are a good candidate; they give rapid, useful estimates of language proficiency. Ideally, several formats are available so that language proficiency can be measured independently of the method used. In the present study, a French C-test was developed and tested on 129 Dutch-French bilingual students. The newly developed C-test was compared to an exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In the reading test of HSK Level 6, there are ten multiple-choice items which require participants to choose one set of correct words from four possible options to complete sentences provided. Such fill-in-the-blank items have been used as cloze tests to measure second language proficiency (Cromheecke & Brysbaert, 2022 ; Oller, 1973 ; Tremblay, 2011 ). The cloze test in our study was not generated by using the sample exam papers provided on the HSK official website because these free resources are easily accessible to participants.…”
Section: Methodsmentioning
confidence: 99%
“…In the reading test of HSK Level 6, there are ten multiple-choice items which require participants to choose one set of correct words from four possible options to complete sentences provided. Such fill-in-the-blank items have been used as cloze tests to measure second language proficiency (Cromheecke & Brysbaert, 2022 ; Oller, 1973 ; Tremblay, 2011 ). The cloze test in our study was not generated by using the sample exam papers provided on the HSK official website because these free resources are easily accessible to participants.…”
Section: Methodsmentioning
confidence: 99%
“…Were this the case, meaning recall and meaning recognition vocabulary knowledge could possibly be considered separate measures that uniquely contribute to predicting reading ability and could in fact be deployed in tandem as part of multicomponential models of reading ability. Rather than attempting to identify a single best test, the two modalities might better be treated as two imperfect vocabulary measures that are better utilized as manifest variables under a latent variable approach to vocabulary knowledge modeling (Cromheecke & Brysbaert, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meaning recall, meaning recognition, reading, TOEIC, vocabulary testing A continuing debate in L2 vocabulary research relates to which modality of vocabulary knowledge displays the strongest correlation with reading proficiency, with some researchers favoring tests of meaning recall knowledge (McLean et al, 2020), and others arguing that meaning recognition tests are the superior predictor (Laufer & Aviad-Levitzky, 2017). While a recent meta-analysis indicated that, on average, meaning recall measures have superior predictive power to meaning recognition (S. Zhang & Zhang, 2020), other researchers argued that these modalities should be treated as multiple imperfect measures that could be used in unison as manifest variables under a latent variable approach (Cromheecke & Brysbaert, 2022). There is a theoretical basis for this latter approach in vocabulary research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation